Assessment of Replicability and Efforts to Refine an Operant Conditioning Procedure for Larval Zebrafish - Christian Agrillo; Eleonora Rovegno; Marco Dadda; Cristiano Bertolucci; Angelo Bisazza (Animals)
The zebrafish model is rapidly advancing numerous areas of basic and translational research, including toxicology, drug discovery, molecular genetics, genomic research, developmental biology, and the study of human diseases (reviewed in [...]